The prevalence of atopic dermatitis history in asthmatic children - Rifda Suryati; Arwin AP Akib; I Boediman; Abdul Latief (Indonesian Pediatric Society, 2006)
Background Atopic dermatitis (AD) is a risk factor of asthma. Thereis still limited information about its prevalence and characteristicsin asthmatic children.Objective To find out the prevalence of AD history in asthmaticchildren.Methods This was a cross-sectional study conducted at the De-partment of Child Health, Cipto Mangunkusumo Hospital, Jakarta,from July until December 2004. Patients with asthma who were ator less than 5 years of age were included in the study. The parentshad completed study questionnaire about asthma, AD, and someinformation about atopic family history, the food history in infantperiod and environment factors.Results Ninety children met the inclusion criteria. Male and femaleratio was 1.5:1. Most of subjects reported onset of asthma in 12-36 months of age. The history of AD was found in 26% of asth-matic children with quite similar number for both sexes. All sub-jects had atopic family history with asthma as the most commonmanifestation. The environment factors contributed to this eventwere mother’s diet containing allergen and smoking history in familyduring pregnancy and lactation period. More than half of subjectshad no breast-feeding. Solid food and formulated milk had beenearly-introduced.Conclusion History of AD is found in 26% asthmatic children.The percentage of characteristic distribution of factors which hadbeen assumed has a role in asthma and AD was similarly equalbetween subjects with and without history of AD